Large second harmonic generation enhancement in Si3N4 waveguides by all-optically induced quasi-phase-matching - Adrien Billat (Nature Portfolio, 2017)
Phase-matching and quasi-phase-matching in periodically poled ferroelectrics ensure efficient harmonic generation, but only statically. Here, Billat et al. demonstrate all-optically reconfigurable second harmonic generation by inscribing a stable grating in CMOS-compatible nonlinear waveguides.